Differential activation of signalling factors following low and high dose of gamma radiation in vivo. (4th October 2004) - Mitra, Anirban K.; Singh, Rakesh K.; Narang, Himanshi; Krishna, M., Sanjeev K. Maurya
The activation of signalling molecules that contribute to the development of radioresistance following radiotherapy was investigated following irradiation with very low doses (0.1 and 0.5 Gy) and high dose (1 and 3 Gy) of γ radiation. Expression of protein kinase C (PKC) was isoform specific. There was a marked difference in the response of ERK 44/42, which is known to confer radioresistance on the tumour cell. The expression at low dose was persistent till 24 hrs with a reappearance at 7 days, while the response at high dose (3 Gy) was transient, an activation at 4 hrs with a return to normal values at the subsequent time periods. These studies indicate that data obtained at high doses should not be extrapolated to low doses. The response of each signalling factor is different at different doses. Since radioadaptation and the development of radioresistance is a low dose phenomenon, ERK 44/42 seems to be the most relevant among the signalling factors.